The Role of Architecture in the Identification of Obstacles and Spatial Solutions to Inclusive Education - Ayesha M. Malik; Memona Rashid; Muhammad Yusuf Awan; Iram Batool Alvi (University of Management and Technology, 2018)
Education is the basic right of every child. However, there are many barriers to education for children with special needs. These special needs are due to their physical or physiological make up and are the reason they often feel desolated, mostly due to the lack of educational facilities required to fulfill those needs that should be available for all. This conceptual paper attempts to outline the term 'inclusive education' in terms of the democratic principles established by the international community. The paper also attempts to discuss Pakistan's progress in adopting inclusive education by analyzing the current institutional framework of the education sector and infrastructure constraints in mainstream schools. Various case studies about educational centers in Pakistan's urban hubs have been analyzed also to learn more about the impediments in this regard. Moreover, data has been collected from 25 districts of Punjab to learn about the current status of public schools and to know whether or not they have been transformed into inclusive schools. Findings show that building design is a major barrier among other challenges. Building layout of an inclusive school has been presented as a model for making existing schools more inclusive for students with various disabilities, so that benefits of inclusion are drawn not only by the disabled but also by mainstream students.